Transport, tourism and technology in Portugal between the late 19th and early 20th centuries - Matos, Ana Cardoso de (2010)
In recent years, tourism has experienced increasing interest from researchers in various areas, a fact that has resulted not only in a diversity of approaches from which this theme can be treated, but also in the uncovering of the interconnections that exist between tourism and the development of the economy of transport and of society2. Thus, tourist growth in each country has been the subject of several studies, ranging from economics to the political and cultural aspects associated with publicising the country as well as to the links between tourism and transport developments3. Research on the institutions promoting tourism and the magazines in which it is advertised has led to an understanding of the role that professionals such as engineers have played in promoting the activity and how they have long regarded it as a form of development for the economy4 and for transport5. The study of travel guides is another possible approach to understanding the links between tourism and transport. Utilitarian in their nature, travel guides are a reflection of the economic, social, cultural and technological changes that, over time, have been introduced into travel for cultural purposes or for summer vacations, and which gradually have come to be participated in by increasingly larger social groups6. The analysis of various tourist guides allows for an approach to various themes, particularly the different forms of transport and the new industries that technological and industrial development have made available for travellers/tourists. Analysing the 20th century tourism phenomenon thereby implies understanding all the economic, social, political and technological changes that were initiated in the second half of the 18th century and which eventually brought about today’s phenomenon of ‘mass tourism’. Access to tourist travel – for improving knowledge, for leisure or even for therapeutic reasons – at the beginning of the 18th century, a privilege of the aristocracy, was gradually extended to include the rich bourgeoisie. Throughout the 19th century, it embraced even wider social strata through the development of transport and communications. However, in the 20th century its high level of growth allowed tourism to become, for many regions and even for some countries, one of the main sources of income and an important support for the economy.7 Throughout the 20th century, new achievements were established in the world of work, such as the right to paid holidays, which contributed largely to increase the numbers of those who could spend their leisure time getting to know other places and other cultures. Many of the changes that occurred in tourism were determined by the technological and industrial innovations that generated an increase in and a broadening of new means of transport. As Catherine Bertho Lavenir observes, "les voyages changent comme changent les techniques" (Lavenir 1999: 9). According to this author, today’s characteristics of tourism are the result of an evolution marked by three distinct moments, separated by technological changes. The first period was the age of coaches and railways. Shortly before the turn of the century, the bicycle and the automobile changed the travelling conditions, allowing travellers a greater mobility and freeing them from the pre-defined routes offered by the railways. In the middle of the 20th century, the expansion of road transport as well as the development of maritime transport and the increase in air transport allowed tourism travel to be undertaken by an even broader spectrum of the population (Lavenir 1999: 9–11). This text seeks to examine the links that, from the late 19th century into the early decades of the 20th, were established in Portugal between tourism and transport, connecting them with the strategies followed by railway companies, cycling associations, the Automobile Club of Portugal (1903) and Sociedade de Propaganda de Portugal (1906) in the promotion of tourism travel within Portugal and abroad.